2014
DOI: 10.1159/000366398
|View full text |Cite
|
Sign up to set email alerts
|

�-Elemene Reverses Chemoresistance of Breast Cancer via Regulating MDR-Related MicroRNA Expression

Abstract: Background: Multidrug resistance (MDR) directly contributes to the clinical failure of chemotherapy in breast cancer (BCA). β-elemene is a natural antitumor drug from plants. We previously confirmed that MDR could be reversed by β-elemene. In this study, we intended to investigate the reversal effect of β-elemene on MDR in human BCA adriacin (Adr) -resistant MCF-7 cells (MCF-7/Adr) and docetaxel (Doc) - resistant MCF-7 cells (MCF-7/Doc) through the gene regulatory network. Methods: MTT-cytotoxic, miRNA microar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 20 publications
3
35
0
Order By: Relevance
“…The P-gp expression pattern of exosomes was similar to that of the original cells [17]. In addition, we confirmed that β-elemene could regulate the expression of the target genes PTEN and Pgp [11]. We utilised Western blot analysis to determine whether the potential expression of PTEN and Pgp changes in exosomes.…”
Section: β-Elemene Treatment Alters the Expression Of Pten And Pgp Prsupporting
confidence: 67%
See 2 more Smart Citations
“…The P-gp expression pattern of exosomes was similar to that of the original cells [17]. In addition, we confirmed that β-elemene could regulate the expression of the target genes PTEN and Pgp [11]. We utilised Western blot analysis to determine whether the potential expression of PTEN and Pgp changes in exosomes.…”
Section: β-Elemene Treatment Alters the Expression Of Pten And Pgp Prsupporting
confidence: 67%
“…These exosomes could alter chemo-susceptibility in recipient sensitive cells, which partly contributes to the successful intercellular transfer of MDR-specific miRNAs and results in the reversal of the BCA chemoresistance [10]. We also confirmed that β-elemene could influence MDR-related miRNA expression and regulate the expression of the target genes PTEN and Pgp, which may lead to the reversal of the chemoresistant breast cancer cells [11]. However, no report has demonstrated the mechanisms of β-elemene in reversing MDR in BCA from exosomes.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…In addition, despite the great advances achieved in radiotherapy and cytotoxic drug development, long term cure rates by standard therapies are disappointing owing to disseminated disease at diagnosis and chemotherapeutic resistance [148]. Ectopic miRNAs are involved in various drug resistant mechanisms including EMT, CSC, apoptosis avoidance, androgen signaling and multiple drug resistance (MDR) transporters [78,149,150]. Additionally, miR-100 can influence the sensitivity of tumors to chemo-or radiation therapy, so a combination of miR-100 chemo-or radiation therapy proves to be a novel antitumor strategy.…”
Section: Mir-100 In Cancer Therapymentioning
confidence: 99%
“…Thus, understanding of the mechanisms underlying the growth of BC is extremely important for its therapy [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%